PENGARUH VARIABEL MAKRO EKONOMI (BI RATE, KURS, HARGA EMAS DAN HARGA MINYAK DUNIA) TERHADAP INDEKS REKSA DANA DI INDONESIA TAHUN 2010 - 2012 - , Jemi Alwan Rinaldi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this research is to analyze the impact of macro economic variables on return index mutual fund employing data between 2010 and 2012. It provides three models for the dependent variable is separated into return on index equity fund, return on index balanced fund and return on index fixed income fund. This study use four macro economic variables: BI rate, exchange rate, gold price and oil price. Their role as independent variables. Multiple regression linear is applied to the data, also ordinary least square model is utilized. In addition, this research is divided into two versions with an estimated weekly and monthly observations. Estimated result with weekly data showed that exchange rates have negative impact on all three models, namely are return on index equity fund, return on index balanced fund and return on index fixed income fund. While the positive impact of oil prices on both models is the return on index equity fund and return on index balanced fund. For return on index fixed income fund, the independent variable has positive impact is gold prices. The ordinary least square estimates are inefficient because they contain unnormal distributed data in the three models. While the return on index equity fund and return on index balanced fund index return are on the classical assumption test are autocorrelation and heteroskedasticity. The results on the regression model with monthly observations showed that exchange rate have impact on all three models, namely are return on index equity fund, return on index balanced fund and return on index fixed income fund. Other independent variables have no effect. Regression model with monthly have passed classical assumption test.